Privacy Protection for Personal Health Device Communication and Healthcare Building Applications - Soon Seok Kim; Yong Hee Lee; Jong Mo Kim; Deok Seok Seo; Gwang Hee Kim; Yoon Seok Shin (Journal of Applied Mathematics)
This paper proposes a new method for protecting patient privacy when communicating with a gateway which collects bioinformation through using personal health devices, a type of biosensor for telemedicine, at home and in other buildings. As the suggested method is designed to conform with ISO/IEEE 11073-20601, which is the international standard, interoperability with various health devices was considered. We believe it will be a highly valuable resource for dealing with basic data because it suggests an additional standard for security with the Continua Health Alliance or related international groups in the future.